Verbatim report of the judgment in the case of Baxter v. Langley, delivered by Mr. Justice Byles, in the Court of Common Pleas, Westminster Hall, on Thursday, November 19th, 1868 (Austin, 1868)
At the top of the titlepage : Sunday evenings for the people.